Diseño y estructuración de un modelo de gestión administrativo-financiero, para la prestación de servicios de calidad en empresas de medicina prepagada - Oyos Acurio, Doris Mariela (2007)
In this general context, this work will be done in order to propose a "Model Administrative and Financial Management for the provision of quality services in the health area and more specifically in Prepaid Medicine" in "the company HEALTH SA "which is optimal and applicable to the organization which in turn allows efficient management to increase the level of economic growth and generate leads for the company added value for customers and.